A Meta-Analysis of Choroidal Thickness Changes in Unilateral Amblyopia - Liu, Yanli (J Ophthalmol, 2017)
PURPOSE: To date, the topic of amblyopic changes remains controversial. Therefore, a systematic review and meta-analysis were carried out to evaluate choroidal changes in unilateral amblyopia. METHODS: Major literature databases were searched for amblyopia-relevant studies. Using enhanced depth imaging optical coherence tomography (EDI-OCT), the primary outcome parameters examined were subfoveal choroidal thickness (SFCT) and different choroidal thickness (CT) positions. Efficacy estimates were evaluated by weighted mean difference (WMD) and 95% confidence interval (CI) for choroidal-associated changes. We performed subgroup analysis and metaregression analysis to examine potential sources of heterogeneity. RESULTS: Eleven cross-sectional studies that included a total of 768 participants were identified. The amblyopic eye SFCT was thicker than that of the fellow and control (normal) eyes (WMD(amblyopia versus fellow) = 49.24, 95% CI of 30.22 to 68.27, p < 0.001; WMD(amblyopia versus control) = 54.51, 95% CI of 32.17 to 76.85, p < 0.001). There were no differences between the fellow and control eyes (WMD = 13.81, 95% CI of 1.16 to 28.77, p = 0.071). Subgroup and metaregression analyses indicated that the OCT type was the main source of heterogeneity. CONCLUSIONS: The CT in the amblyopic eyes was thicker than that in the fellow and control eyes.